Negative pole piece, preparation method thereof and battery
By using nano SiO2 and polyacrylic acid to form a cladding layer in the negative electrode sheet of lithium-ion batteries, the problem of high volume expansion of silicon-based materials is solved, the cycle performance of the battery and the efficiency of the Coulomb are improved, and the battery life is extended.
Patent Information
- Application Number
- CN202411320939.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
AI Technical Summary
The volume expansion rate of silicon-based materials in lithium-ion batteries is high during charging and discharging, resulting in powdered and unstable SEI film formation, affecting battery performance.
NanoSiO2 and polyacrylic acid are used in the negative electrode sheet to form a stable cladding layer, which reduces the volume expansion of the silicon-based material, and improves the adhesion and conductivity of the active material, reducing the penetration and side reaction of the electrolyte.
By forming a stable cladding layer, the cycling performance and Coulomb efficiency of the battery are improved, the ion transmission impedance is reduced, and the battery life is extended.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a preparation method thereof, and a battery. Background Art
[0002] Lithium-ion batteries are widely used in electric vehicles and portable electronic products due to their high specific capacity, long cycle life and low self-discharge rate. However, lithium-ion battery technology still faces anxiety about battery life and mileage, and it is difficult to further improve energy density.
[0003] Lithium-ion battery negative electrode materials mainly include graphite, silicon-based materials and other alloy materials. Although graphite has been commercialized, its theoretical specific capacity is only 372mA·h / g, which is difficult to meet the needs of high energy density batteries. In contrast, the theoretical specific capacity of silicon-based materials is as high as 4200mA·h / g, and has a lower lithium insertion and extraction potential (<0.5V vs Li + / Li), which is a very promising negative electrode material.
[0004] However, the volume expansion rate of the silicon negative electrode during the charging and discharging process is as high as 300%, which may cause the silicon-based material to pulverize and the active material to separate from the current collector. An unstable solid electrolyte interphase (SEI film) will form on the surface of the silicon negative electrode, consuming lithium ions and affecting battery performance. Summary of the invention
[0005] The embodiments of the present invention provide a negative electrode plate and a method for preparing the same, as well as a battery, which can improve the technical problem of high volume expansion rate of silicon-based materials in existing negative electrode plates.
[0006] In the first aspect, an embodiment of the present invention provides a negative electrode plate, comprising a current collector and a negative electrode material layer and a coating layer sequentially arranged on the current collector in a direction away from the current collector, wherein the material of the negative electrode material layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-based material, and the material of the coating layer comprises nano-SiO2 and polyacrylic acid.
[0007] In one embodiment, the D50 particle size of the nano-SiO2 is ≤200nm; and / or,
[0008] The mass ratio of the nano-SiO2 to the polyacrylic acid is (0.5-1.5):10; and / or,
[0009] The mass percentage of the silicon-based material in the negative electrode active material is ≤12%; and / or,
[0010] The coating layer has a thickness of 0.7 μm-1.3 μm.
[0011] In one embodiment, the material of the negative electrode material layer further includes a conductive agent, and the mass ratio of the silicon-based material to the conductive agent is (8-12):1;
[0012] The material of the negative electrode material layer also includes a binder, and the mass ratio of the binder to the silicon-based material is (0.022-0.078):1; and / or,
[0013] The negative electrode active material further comprises graphite; and / or,
[0014] The silicon-based material includes one or more of silicon carbon and silicon oxygen.
[0015] In one embodiment, the material of the negative electrode material layer further includes a conductive agent, and the conductive agent includes one or more of conductive carbon black, nano-carbon fibers and carbon nanotubes; and / or,
[0016] The material of the negative electrode material layer also includes a binder, and the binder includes polyacrylic acid and carboxymethyl cellulose, and the mass ratio of the carboxymethyl cellulose to the polyacrylic acid is (0.1-0.3):1.
[0017] In a second aspect, an embodiment of the present invention provides a method for preparing a negative electrode sheet, comprising the following steps:
[0018] Providing a current collector and a negative electrode material layer slurry, wherein the negative electrode material layer slurry includes a negative electrode active material and a first solvent, wherein the negative electrode active material includes a silicon-based material, disposing the negative electrode material layer slurry on the surface of the current collector to obtain a first wet film layer, and performing a first drying on the first wet film layer to form a negative electrode material layer;
[0019] A coating layer slurry is provided, wherein the coating layer slurry includes nano-SiO2, polyacrylic acid and a second solvent. The coating layer slurry is disposed on the surface of the negative electrode material layer to obtain a second wet film layer. The second wet film layer is subjected to a second drying to form a coating layer, thereby obtaining a negative electrode sheet.
[0020] In one embodiment, the solid content of the negative electrode material layer slurry is 45%-65%.
[0021] In one embodiment, the method for preparing the negative electrode material layer slurry comprises the following steps:
[0022] Mixing the binder and the first solvent to obtain a binder glue solution;
[0023] The negative electrode active material and the conductive agent are mixed and then mixed with the binder paste to obtain the negative electrode material layer slurry.
[0024] In one embodiment, the binder includes polyacrylic acid and carboxymethyl cellulose, and the binder and the first solvent are mixed to obtain a binder glue solution, including:
[0025] Mixing the carboxymethyl cellulose and the first solvent to obtain a carboxymethyl cellulose glue;
[0026] The polyacrylic acid and the first solvent are mixed to obtain a polyacrylic acid glue solution, and the binder glue solution includes the carboxymethyl cellulose glue solution and the polyacrylic acid glue solution.
[0027] In one embodiment, the solid content of the carboxymethyl cellulose glue is 0.5%-3%; and / or,
[0028] The solid content of the polyacrylic acid glue is 3%-9%.
[0029] In one embodiment, the first drying temperature is 75° C. to 105° C., and the first drying time is 15 min to 25 min; and / or
[0030] The temperature of the second drying is 45° C. to 55° C., and the time of the second drying is 8 min to 12 min.
[0031] In one embodiment, the method for preparing the coating layer slurry comprises the following steps: mixing nano-SiO2 and polyacrylic acid in a second solvent to obtain the coating layer slurry.
[0032] In a third aspect, an embodiment of the present invention provides a battery, comprising the above-mentioned negative electrode plate.
[0033] Beneficial effects of the embodiments of the present invention:
[0034] In an embodiment of the present invention, by arranging nano-SiO2 and polyacrylic acid on the surface of the negative electrode material layer, the silicon-oxygen bonds of nano-SiO2 and the carboxyl groups of polyacrylic acid can form hydrogen bonds, thereby forming a stable coating layer, which can reduce the volume expansion of the silicon-based material and improve the battery performance. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state; while "inside" and "outside" refer to the outline of the device.
[0036] In order to ensure battery performance, a small amount of silicon-based material is usually added to the negative electrode to increase the gram capacity of the composite negative electrode material. However, after adding graphite to the silicon-based material, problems such as first-cycle efficiency, cycle performance and battery cell expansion will still occur, which hinders the large-scale application of silicon-based materials.
[0037] The technical solution of this application is as follows:
[0038] In a first aspect, an embodiment of the present application provides a negative electrode plate, comprising a current collector and a negative electrode material layer and a coating layer sequentially arranged on the current collector in a direction away from the current collector, wherein the material of the negative electrode material layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-based material, and the material of the coating layer comprises nano-SiO2 and polyacrylic acid.
[0039] In the present application, by arranging nano-SiO2 and polyacrylic acid on the surface of the negative electrode material layer, the silicon-oxygen bond of nano-SiO2 and the carboxyl group of polyacrylic acid can form a hydrogen bond, thereby forming a stable coating layer, which can reduce the volume expansion of the silicon-based material, so as to improve the bonding force and conductivity between the active materials and improve the electron conduction rate of the electrode; the coating layer can reduce the penetration of the electrolyte, reduce the side reaction between the electrolyte and the active material, and improve the coulomb efficiency and cycle performance of the electrode; the nano-SiO2 material has abundant pore channels, which can provide abundant pores for the coating layer, which can promote Li + transmission, thereby reducing the ion transfer impedance.
[0040] In some embodiments, the D50 particle size of nano-SiO2 is ≤200nm, for example, it can be 200nm, 190nm, 180nm, 170nm, 160nm, 150nm, 140nm, etc. Within this range, SiO2 has a higher specific surface area, which can improve its distribution uniformity in the coating layer and provide sufficient pores for lithium ions to enter and exit.
[0041] In some embodiments, the mass ratio of nano-SiO2 to polyacrylic acid is (0.5-1.5):10. For example, it can be 0.5:10, 0.6:10, 0.7:10, 0.8:10, 0.9:10, 1.0:10, 1.1:10, 1.2:10, 1.3:10, 1.4:10, 1.5:10. Within this range, lithium ions can be effectively transmitted through the coating layer. Too little silicon dioxide and too much polyacrylic acid will form a coating with high density and few pores, which will hinder the transmission of lithium ions; too much silicon dioxide will form a coating with too high a thickness of nano-SiO2, thereby increasing the ion transmission distance and thus increasing the ion transmission impedance.
[0042] In some embodiments, the coating layer has a thickness of 0.7 μm-1.3 μm, for example, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, etc. Within this range, lithium ions can be effectively transmitted through the coating layer, while effectively reducing the volume expansion of the silicon-based material.
[0043] In some embodiments, the silicon-based material includes one or more of silicon carbon and silicon oxygen.
[0044] In some embodiments, the silicon-based material includes silicon carbon.
[0045] In this application, silicon-carbon materials can be prepared by uniformly depositing silicon nanoparticles in a porous carbon material skeleton using a vapor deposition method. Compared with traditional silicon-oxygen and ground silicon-carbon materials, vapor-deposited silicon-carbon materials perform better in terms of battery first-cycle efficiency, energy density, cycle performance, and battery cell expansion, but there is still a large gap with traditional graphite materials and they cannot be completely replaced.
[0046] In some embodiments, the mass percentage of silicon-based materials in the negative electrode active material is ≤ 12%, for example, it can be 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, etc. In this way, the expansion of silicon carbon can be effectively reduced, the volume expansion rate of silicon carbon can be reduced, and the cycle performance decay of the battery can be reduced. If too much silicon carbon is added, the effect of reducing its expansion will be reduced, and the volume expansion rate will increase exponentially, resulting in rapid decay of the cycle performance.
[0047] In some embodiments, the negative electrode active material further includes graphite.
[0048] In some embodiments, the material of the negative electrode material layer further includes a conductive agent.
[0049] In some embodiments, the mass ratio of the silicon-based material to the conductive agent is (8-12):1, for example, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, etc. Within this range, the conductivity of the negative electrode sheet can be improved. The particles of the silicon-based material are smaller and its conductivity is not as good as that of graphite, so the amount of the conductive agent needs to be adjusted to improve its conductivity.
[0050] In some embodiments, the conductive agent includes one or more of conductive carbon black (SP), nanocarbon fiber (VGCF), and carbon nanotube (CNT).
[0051] In some embodiments, the material of the negative electrode material layer further includes a binder, and the mass ratio of the binder to the silicon-based material is (0.022-0.078): 1. Within this range, the bonding effect can be improved.
[0052] In some embodiments, the binder includes polyacrylic acid (PAA) and carboxymethyl cellulose (CMC). Thus, the carboxyl groups in the polyacrylic acid and the hydroxyl groups in the carboxymethyl cellulose can undergo a dehydration condensation reaction to form an ester bond, thereby generating a cross-linked polyacrylic acid-carboxymethyl cellulose (c-PAA-CMC) binder, thereby improving the bonding effect.
[0053] In some embodiments, the mass ratio of carboxymethyl cellulose (CMC) to polyacrylic acid (PAA) is (0.1-0.3):1, for example, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, etc. Within this range, the bonding effect can be improved.
[0054] In a second aspect, an embodiment of the present application provides a method for preparing a negative electrode sheet, comprising the following steps:
[0055] S1. Provide a current collector and a negative electrode material layer slurry, and place the negative electrode material layer slurry on the surface of the current collector to form a negative electrode material layer, wherein the negative electrode material layer slurry includes a negative electrode active material and a first solvent, and the negative electrode active material includes a silicon-based material;
[0056] S2. Provide a coating layer slurry, which includes nano-SiO2, polyacrylic acid and a second solvent. Set the coating layer slurry on the surface of the negative electrode material layer to form a coating layer to obtain a negative electrode sheet.
[0057] In some embodiments, the solid content of the negative electrode material layer slurry is 45%-65%, for example, it can be 45%, 47%, 49%, 51%, 53%, 55%, 57%, 59%, 61%, 63%, 65%, etc. Within this range, the coating stability of the negative electrode material layer slurry can be improved. If the solid content of the negative electrode material layer slurry is too high, its fluidity is poor and the coating surface density stability is poor; if the solid content of the negative electrode material layer slurry is too low, its fluidity is too good, the coating peeling force is low, and the pole piece is easy to crack.
[0058] In some embodiments, the solid content of the negative electrode material layer slurry is 50%-60%, for example, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, etc. Within this range, the coating stability of the negative electrode material layer slurry can be fully improved.
[0059] In some embodiments, the method for preparing the negative electrode material layer slurry comprises the following steps:
[0060] Mixing the binder and the first solvent to obtain a binder glue solution;
[0061] The negative electrode active material and the conductive agent are mixed and then mixed with a binder paste to obtain a negative electrode material layer slurry.
[0062] In some embodiments, the binder includes polyacrylic acid and carboxymethyl cellulose, and the step of mixing the binder and the first solvent to obtain a binder glue solution includes:
[0063] Mixing the carboxymethyl cellulose (CMC) and the first solvent to obtain a carboxymethyl cellulose glue;
[0064] The polyacrylic acid (PAA) and the first solvent are mixed to obtain a polyacrylic acid glue solution, and the binder glue solution includes the carboxymethyl cellulose glue solution and the polyacrylic acid glue solution.
[0065] In the present application, the solvents in the carboxymethyl cellulose glue and the polyacrylic acid glue may be the same or different.
[0066] In some embodiments, the solid content of the carboxymethyl cellulose glue is 0.5%-3%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc. Within this range, the mixing uniformity of the glue and the active material can be improved while ensuring the adhesive force of the glue. If the solid content of the glue is too high, the glue will be very viscous and it will be difficult to stir evenly after adding the active material; if the solid content of the glue is too low, the adhesive force of the glue is insufficient.
[0067] In some embodiments, the solid content of the carboxymethyl cellulose glue is 1%-2%, for example, it can be 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, etc.
[0068] In some embodiments, the solid content of the polyacrylic acid glue is 3%-9%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, etc. Within this range, the mixing uniformity of the glue and the active material can be improved while ensuring the adhesive force of the glue. If the solid content of the glue is too high, the glue will be very viscous and it will be difficult to stir evenly after adding the active material; if the solid content of the glue is too low, the adhesive force of the glue is insufficient.
[0069] In some embodiments, the solid content of the polyacrylic acid glue is 5%-7%, for example, it can be 5%, 5.2%, 5.4%, 5.6%, 5.8%, 6%, 6.2%, 6.4%, 6.6%, 6.8%, 7%, etc.
[0070] In some embodiments, the negative electrode material layer slurry is disposed on the surface of the current collector to form a negative electrode material layer, including:
[0071] The negative electrode material layer slurry is coated on the surface of the current collector and first dried to form a negative electrode material layer.
[0072] In some embodiments, the first drying temperature is 75°C to 105°C, for example, it can be 75°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, etc., and the first drying time is 15min to 25min, for example, it can be 15min, 17min, 19min, 21min, 23min, 25min, etc.
[0073] In some embodiments, the coating layer slurry is disposed on the surface of the negative electrode material layer to form a coating layer, comprising:
[0074] The coating layer slurry is applied to the surface of the negative electrode material layer and subjected to a second drying to form a coating layer.
[0075] In some embodiments, the second drying temperature is 45°C to 55°C, for example, it can be 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, etc., and the second drying time is 8min to 12min, for example, it can be 8min, 9min, 10min, 11min, 12min, etc.
[0076] In some embodiments, the method for preparing the coating layer slurry comprises the following steps:
[0077] Nano-SiO2 and polyacrylic acid (PAA) are provided and mixed in a solvent to obtain a coating layer slurry.
[0078] In some embodiments, nano-SiO2 and polyacrylic acid (PAA) are provided and mixed in a solvent, including: providing nano-SiO2 and polyacrylic acid (PAA), adding them into a solvent and performing ultrasonic stirring.
[0079] In some embodiments, the ultrasonic stirring time is 0.5h-1.5h, for example, it can be 0.5h, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, etc.
[0080] The materials and parameters used in the method for preparing a negative electrode plate provided in the embodiment of the present application are as described above.
[0081] In a third aspect, an embodiment of the present application provides a battery, comprising the above-mentioned negative electrode plate.
[0082] Example 1
[0083] A negative electrode sheet and a method for preparing the same, comprising the following steps:
[0084] (1) Add nano-SiO2 (particle size D50: 200 nm) and polyacrylic acid (PAA) in a mass ratio of 1:10 into 20 ml of ethanol and stir ultrasonically for 1 h to obtain a coating layer slurry;
[0085] (2) mixing carboxymethyl cellulose (CMC) with water and stirring for 5 hours to obtain a carboxymethyl cellulose glue solution with a solid content of 1.5%;
[0086] (3) mixing polyacrylic acid (PAA) and water and stirring for 4 hours to obtain a polyacrylic acid glue solution with a solid content of 6%;
[0087] (4) Premixing graphite, silicon carbon (prepared by vapor deposition method) and conductive carbon black (SP) dry powder at a mass ratio of 88:12:1 for 30 minutes, adding carboxymethyl cellulose glue and polyacrylic acid glue (the amount of polyacrylic acid glue added satisfies: the mass ratio of polyacrylic acid in the polyacrylic acid glue to silicon carbon is 0.04:1, and the amount of carboxymethyl cellulose glue added satisfies: the mass ratio of carboxymethyl cellulose in the carboxymethyl cellulose glue to polyacrylic acid in the polyacrylic acid glue is 0.2:1) and stirring for 3 hours, and then adding N-methylpyrrolidone (NMP) to adjust the solid content of the slurry to 55%, thereby obtaining a negative electrode material layer slurry;
[0088] (5) The prepared negative electrode material layer slurry is evenly coated on the surface of the copper foil and dried in an oven at 90° C. for 20 min to form a negative electrode material layer;
[0089] (6) The coating layer slurry was uniformly coated on the surface of the negative electrode material layer, and then dried in a vacuum oven at 50° C. to form a coating layer with a thickness of 1 μm to obtain a negative electrode sheet.
[0090] Example 2
[0091] This embodiment is basically the same as Embodiment 1, except that the mass ratio of nano-SiO2 to polyacrylic acid in the coating layer slurry in this embodiment is 0.5:10.
[0092] Example 3
[0093] This embodiment is basically the same as Embodiment 1, except that the mass ratio of nano-SiO2 to polyacrylic acid in the coating layer slurry in this embodiment is 1.5:10.
[0094] Example 4
[0095] This embodiment is substantially the same as Embodiment 1, except that the particle size D50 of the nano-SiO2 in this embodiment is 150 nm.
[0096] Example 5
[0097] This embodiment is substantially the same as Embodiment 1, except that the particle size D50 of the nano-SiO2 in this embodiment is 100 nm.
[0098] Example 6
[0099] This embodiment is substantially the same as Embodiment 1, except that the solid content of the carboxymethyl cellulose glue in this embodiment is 0.5%.
[0100] Example 7
[0101] This embodiment is substantially the same as Embodiment 1, except that the solid content of the carboxymethyl cellulose glue in this embodiment is 3%.
[0102] Example 8
[0103] This embodiment is basically the same as Embodiment 1, except that the solid content of the polyacrylic acid glue in this embodiment is 5%.
[0104] Example 9
[0105] This embodiment is basically the same as Embodiment 1, except that the solid content of the polyacrylic acid glue in this embodiment is 7%.
[0106] Example 10
[0107] This embodiment is substantially the same as the embodiment 1, except that the amount of polyacrylic acid glue added in this embodiment satisfies that the mass ratio of polyacrylic acid in the polyacrylic acid glue to silicon carbon is 0.06:1.
[0108] Embodiment 11
[0109] This embodiment is substantially the same as the embodiment 1, except that the amount of the polyacrylic acid glue solution added in this embodiment satisfies that the mass ratio of the polyacrylic acid in the polyacrylic acid glue solution to the silicon carbon is 0.02:1.
[0110] Example 12
[0111] This embodiment is substantially the same as Embodiment 1, except that the particle size D50 of the nano-SiO2 in this embodiment is 250 nm.
[0112] Example 13
[0113] This embodiment is basically the same as Embodiment 1, except that the mass ratio of nano-SiO2 to polyacrylic acid in the coating layer slurry in this embodiment is 2.5:10.
[0114] Embodiment 14
[0115] This embodiment is substantially the same as Embodiment 1, except that the mass ratio of graphite, silicon carbon, and conductive carbon black (SP) in this embodiment is 76:24:2.
[0116] Comparative Example 1
[0117] This comparative example is basically the same as Example 1, except that the negative electrode plate in this comparative example is not provided with a coating layer.
[0118] Comparative Example 2
[0119] This comparative example is basically the same as Example 1, except that in this comparative example, polyacrylic acid (PAA) in the coating layer slurry is replaced by polyvinylidene fluoride (PVDF).
[0120] Battery production:
[0121] The positive electrode uses ternary material lithium iron phosphate as the positive electrode active material, the negative electrode uses the negative electrode plate obtained in the embodiment and the comparative example, and the separator uses PE separator. The positive electrode, separator and negative electrode are stacked in order, and a battery cell is obtained through a stacking process. The battery cell is placed in an outer packaging shell, dried, and injected with electrolyte at an electrolyte injection coefficient of 3.6g / Ah (LiPF6 is dissolved in a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a molar concentration of 1.2mol / L in a mass ratio of 3:7). After vacuum packaging, standing, formation, and capacity separation processes, a lithium-ion battery is obtained.
[0122] Test example:
[0123] Standard charging method: The obtained lithium-ion battery is charged at 4.25V, 0.33C constant current and constant voltage, with a cut-off current of 0.05C. After full charging, the negative electrode rebound is reduced.
[0124] Cycle capacity retention rate test method: The obtained lithium ion battery is charged to 3.65V at 25°C and 1C constant current, and then discharged to 2.5V at 1C constant current, and cycled 500 times to obtain the cycle capacity retention rate.
[0125] Peeling force test method: The width and length of the negative electrode sheets obtained in the examples and comparative examples were fixed by a peeling force tester, the active materials were adhered with tape, and the peeling strength of the sheets was tested by a tensile tester.
[0126] Coulombic efficiency: The discharge capacity of a lithium-ion battery divided by the charge capacity.
[0127] Full charge rebound rate: After the obtained lithium-ion battery is fully charged, the thickness of the negative electrode sheet is measured to obtain the fully charged thickness. The fully charged thickness is divided by the thickness of the negative electrode sheet when the lithium-ion battery is empty to obtain the full charge rebound rate.
[0128] Full charge rebound rate after 500 cycles: After the obtained lithium-ion battery is fully charged 500 times, the thickness of the negative electrode sheet is measured to obtain the fully charged thickness. The fully charged thickness is divided by the thickness of the negative electrode sheet when the lithium-ion battery is empty to obtain the full charge rebound rate.
[0129] Table 1
[0130]
[0131] From Table 1, we can see that:
[0132] Compared with Example 12, Example 1, Example 4, and Example 5 have greater peeling force, smaller full-charge rebound rate, smaller full-charge rebound rate after 500 cycles, higher Coulomb efficiency, and higher cycle capacity retention rate after 500 cycles. It can be seen that the particle size of SiO2 will affect the performance of the battery.
[0133] Compared with Example 13, Example 1, Example 2, and Example 3 have greater peeling force, smaller full-charge rebound rate, smaller full-charge rebound rate after 500 cycles, higher Coulomb efficiency, and higher cycle capacity retention rate after 500 cycles. It can be seen that the mass ratio of SiO2 to PAA affects the performance of the battery.
[0134] Compared with Example 14, Example 1 has a greater peeling force, a smaller full-charge rebound rate, a smaller full-charge rebound rate after 500 cycles, a higher Coulomb efficiency, and a higher cycle capacity retention rate after 500 cycles. It can be seen that the mass ratio of graphite to silicon carbon will affect the performance of the battery.
[0135] Compared with Comparative Example 1, the peeling force of the embodiment is greater, the full-charge rebound rate is smaller, the full-charge rebound rate after 500 cycles is smaller, the Coulomb efficiency is higher, and the cycle capacity retention rate after 500 cycles is higher. It can be seen that by arranging nano-SiO2 and polyacrylic acid on the surface of the negative electrode material layer, the battery performance can be improved.
[0136] Compared with Comparative Example 2, the peeling force of the embodiment is greater, the full-charge rebound rate is smaller, the full-charge rebound rate after 500 cycles is smaller, the Coulomb efficiency is higher, and the cycle capacity retention rate after 500 cycles is higher. It can be seen that by arranging nano-SiO2 and polyacrylic acid on the surface of the negative electrode material layer, the battery performance can be improved.
[0137] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A negative electrode plate, characterized in that: It includes a current collector and a negative electrode material layer and a coating layer sequentially arranged on the current collector in a direction away from the current collector. The material of the negative electrode material layer includes a negative electrode active material, which includes a silicon-based material. The material of the coating layer includes nano-SiO2 and polyacrylic acid.
2. The negative electrode sheet according to claim 1, characterized in that: The D50 particle size of the nano-SiO2 is ≤200nm; and / or, The mass ratio of the nano-SiO2 to the polyacrylic acid is (0.5-1.5):10; and / or, The mass percentage of the silicon-based material in the negative electrode active material is ≤12%; and / or, The coating layer has a thickness of 0.7 μm-1.3 μm.
3. The negative electrode sheet according to claim 1, characterized in that: The material of the negative electrode material layer also includes a conductive agent, and the mass ratio of the silicon-based material to the conductive agent is (8-12):1; The material of the negative electrode material layer also includes a binder, and the mass ratio of the binder to the silicon-based material is (0.022-0.078):1; and / or, The negative electrode active material further comprises graphite; and / or, The silicon-based material includes one or more of silicon carbon and silicon oxygen.
4. The negative electrode sheet according to claim 1, characterized in that: The material of the negative electrode material layer further includes a conductive agent, wherein the conductive agent includes one or more of conductive carbon black, nano-carbon fibers and carbon nanotubes; and / or, The material of the negative electrode material layer also includes a binder, and the binder includes polyacrylic acid and carboxymethyl cellulose, and the mass ratio of the carboxymethyl cellulose to the polyacrylic acid is (0.1-0.3):
1.
5. A method for preparing a negative electrode sheet, characterized in that: The following steps are involved: Providing a current collector and a negative electrode material layer slurry, wherein the negative electrode material layer slurry includes a negative electrode active material and a first solvent, wherein the negative electrode active material includes a silicon-based material, disposing the negative electrode material layer slurry on the surface of the current collector to obtain a first wet film layer, and performing a first drying on the first wet film layer to form a negative electrode material layer; A coating layer slurry is provided, wherein the coating layer slurry includes nano-SiO2, polyacrylic acid and a second solvent. The coating layer slurry is disposed on the surface of the negative electrode material layer to obtain a second wet film layer. The second wet film layer is subjected to a second drying to form a coating layer, thereby obtaining a negative electrode sheet.
6. The method for preparing a negative electrode sheet according to claim 5, characterized in that: The solid content of the negative electrode material layer slurry is 45%-65%.
7. The method for preparing a negative electrode sheet according to claim 5, characterized in that: The method for preparing the negative electrode material layer slurry comprises the following steps: Mixing the binder and the first solvent to obtain a binder glue solution; The negative electrode active material and the conductive agent are mixed and then mixed with the binder paste to obtain the negative electrode material layer slurry.
8. The method for preparing a negative electrode sheet according to claim 7, characterized in that: The binder includes polyacrylic acid and carboxymethyl cellulose, and the binder and the first solvent are mixed to obtain a binder glue solution, including: Mixing the carboxymethyl cellulose and the first solvent to obtain a carboxymethyl cellulose glue; The polyacrylic acid and the first solvent are mixed to obtain a polyacrylic acid glue solution, and the binder glue solution includes the carboxymethyl cellulose glue solution and the polyacrylic acid glue solution.
9. The method for preparing a negative electrode sheet according to claim 8, characterized in that: The solid content of the carboxymethyl cellulose glue is 0.5%-3%; and / or, The solid content of the polyacrylic acid glue is 3%-9%.
10. The method for preparing a negative electrode sheet according to claim 5, characterized in that: The first drying temperature is 75° C. to 105° C., and the first drying time is 15 min to 25 min; and / or, The temperature of the second drying is 45° C. to 55° C., and the time of the second drying is 8 min to 12 min.
11. The method for preparing a negative electrode sheet according to claim 5, characterized in that: The method for preparing the coating layer slurry comprises the following steps: mixing nano-SiO2 and polyacrylic acid in a second solvent to obtain the coating layer slurry.
12. A battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet as described in any one of claims 1 to 4 or a negative electrode sheet prepared by the method for preparing the negative electrode sheet as described in any one of claims 5 to 11.
Citation Information
Patent Citations
Silicon-based negative pole piece as well as preparation method and application thereof
CN115000407A
Silicon carbon particle, preparation method thereof, electrochemical device and electronic device
CN117878249A
Image decoding apparatus and image encoding apparatus for adaptive quantization and inverse-quantization, and methods thereby
KR1020240025428A
Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
US20180097223A1
Cited By
Silicon-carbon negative electrode aqueous slurry and preparation method and coating process thereof
CN119560502A